Maize cultivation: present status, major constraints and farmer's perception at Madichaur, Rolpa - Dhakal, S.; Sah, S. K.; Amgain, L. P.; Dhakal, K. H. (Journal of Agriculture and Forestry University, 2022)
Maize (Zea mays) has been one of the most popularly grown crops in the mid hills of Nepal. With a view of assessing the present agronomic management and constraints of maize cultivation, a field survey was carried out in the summer of 2020 at Madichaur, Rolpa, Nepal. Simple random sampling procedure was used to collect data from 100 respondents using a semi structured interview schedule. Information regarding the productivity and adoption of improved technologies by maize growing farmers were also collected. The data were processed and analyzed using MS-Excel and SPSS. Results revealed maize-based cropping system as the major cropping system (65%) with rainy season maize being the dominant one (76%). Varietal selection was primarily based on the local prevalence whereas own preserved seeds were used by majority of the respondents. Local plough was the major tool for land preparation whereas majority of the respondent used FYM as nutrient source and followed sowing behind the plough. Gap filling, thinning, weeding, earthing up was quite common among the respondents, however their intensity varied. External cob storage was the common method of storage. Biotic stress was identified as the major bottleneck for increasing maize productivity followed by lack of irrigation and technical know how.